Analisis Semiotika terhadap Pemberitaan Efisiensi Anggaran Kabinet Prabowo di Kompas TV - Roslia Arfanti; Liliana Muliastuti; Siti Ansoriyah (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study examines the ideological construction of meaning in Kompas TV news reporting on the Prabowo-Gibran cabinet's budget efficiency policy. The news article, published on February 19, 2025, juxtaposes public sector cuts with substantial official uniform allocations, suggesting inherent bias. While previous research has analyzed this text using Peirce's semiotics alone, this paper adopts a multi-theoretical framework incorporating Ferdinand de Saussure, Charles Sanders Peirce, Roland Barthes, and Umberto Eco to achieve a more comprehensive critical analysis. Through qualitative semiotic analysis, the study reveals that linguistic choices such as